2007
DOI: 10.3113/fai.2007.0456
|View full text |Cite
|
Sign up to set email alerts
|

Describing the Medial Longitudinal Arch Using Footprint Indices and a Clinical Grading System

Abstract: Historically, the height of the navicular is considered to be the best approximation of MLA height. The results of this study indicate that the footprint indices are highly correlated with navicular height, indicating that both navicular height measurements and footprint measurements are valid measures of MLA height. Multiple methods exist for measuring the height of the MLA; therefore, it is important to develop a standard set of measurements to be used when foot type is used as a variable in research studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 16 publications
3
98
0
7
Order By: Relevance
“…Villarroya et al [32] also found a significant correlation between footprint-based CA and CSI methods and radiography-based talus-first metatarsal and calcaneal inclination angles. According to a study by Queen et al [27], the inter-rater reliabilities of the CSI and AI were both 0.96, and the between-day reliabilities of the CSI and AI were both 0.91. Because footprint collection requires less time than other methods and can be performed even on a noncooperative child with some assistance, it has been recognized as a simple, effective tool for massive screening for flatfoot in preschool-aged children.…”
Section: Discussionmentioning
confidence: 98%
“…Villarroya et al [32] also found a significant correlation between footprint-based CA and CSI methods and radiography-based talus-first metatarsal and calcaneal inclination angles. According to a study by Queen et al [27], the inter-rater reliabilities of the CSI and AI were both 0.96, and the between-day reliabilities of the CSI and AI were both 0.91. Because footprint collection requires less time than other methods and can be performed even on a noncooperative child with some assistance, it has been recognized as a simple, effective tool for massive screening for flatfoot in preschool-aged children.…”
Section: Discussionmentioning
confidence: 98%
“…17 Numerous studies have attempted to address the issue of comparing medial longitudinal arch height between subject groups by normalizing arch height to foot length or truncated foot length to produce an arch index. 18,19 Because of the significant differences in 9 of the 10 foot anthropometry measures between the two groups in this study, plantar arch height (the only nonsignificant value) was divided by truncated foot length to further investigate this finding. When normalized to truncated foot length, the plantar arch index was significantly less in the obese children compared to the non-obese children (mean±s.d., 0.085±0.018 and 0.098±0.017, respectively, Po0.001).…”
Section: External Foot Measuresmentioning
confidence: 99%
“…Methods using the 2D footprint of the foot have an advantage in a simple application and calculation. According to some sources they show a good repeatability (Nikolaidou, 2006) and inter-and intra-observer reliability (Queen, 2007). However, the bones, the soft tissue, and the associated joint stresses inside the foot were less investigated and remained unclear.…”
Section: Introductionmentioning
confidence: 99%